HUBUNGAN POLA TIDUR DENGAN PRESTASI AKADEMIK PADA MAHASISWA SEMESTER IV T.A. 2017-2018 PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS SAM RATULANGI - Pua, Maleakhi Evan D.; Kepel, Billy J.; Rompas, Sefti (JURNAL KEPERAWATAN, 2018)
Abstract : Sleep is one of the most important process for human, because when someone’s sleep, naturally initiating a neural function and muscle healing process that can cause a benefit to restore someone’s condition when someone’s exhausted. Academic achievement was a study success measuring tools of students and decided by a evaluation system report. The Purpose of this research is to knowing the correlation between sleep pattern and the academic achievement to the students of nursing science programme, medical faculty, Sam Ratulangi University Manado. The Research Methods an analytic survey with retrospective approach. The sample was taken with Purposive Sampling technique with total 36 samples. The instrument that have been used to this research wasa Pittsburgh Sleep Quality Index questionnaire and a observation sheet of 4thsemester academic report card. The Result of this research by using the analytic statistical test Chi Square Continuity Correction with level of significance α = 0,05 or 95%. Result of the statistical test shows P Value = 0,037. The Conclution of this research are there is a correlation between sleep pattern and the academic achievement to the students of Nursing Science Programme, Medical Faculty, Sam Ratulangi University Manado. Keywords: Sleep Pattern, Academic Achievement, Students Abstrak : Tidur adalah suatu proses yang sangat penting bagi manusia, karena saat tidur terjadi proses pemulihan fungsi saraf dan otot secara alami yang bermanfaat mengembalikan kondisi seseorang pada keadaan semula ketika mengalami kelelahan. Prestasi Akademik merupakan alat ukur keberhasilan studi mahasiswa, dan ditentukan melalui sistem penilaian evaluasi. Tujuan penelitian ini adalah untuk mengetahui hubungan pola tidur dengan prestasi akademik pada mahasiswa Program Studi Ilmu Keperawatan Universitas Sam Ratulangi Manado. Metode Penelitian ini bersifat survei analitik dengan pendekatan retrospektif. Sampel diambil dengan teknik pengambilan Purposive Sampling yaitu sebanyak 36 sampel. Instrumen yang digunakan dalam penelitian ini adalah kuesioner Pittsburgh Sleep Quality Index (PSQI) dan lembar observasi Kartu Hasil Studi (KHS) Semester IV. Hasil penelitian menggunakan analisis uji statistik Chi Square Continuity Correction dengan tingkat kemaknaan α = 0,05 atau 95%. Hasil uji statistik didapatkan nilai P = 0,037. Kesimpulan dari penelitian ini yaitu ada hubungan pola tidur dengan prestasi akademik pada mahasiswa Program Studi Ilmu Keperawatan Universitas Sam Ratulangi Manado. Kata Kunci : Pola Tidur, Prestasi Akademik, Mahasiswa